COVID-19: Insights from innovation economists. (1st July 2020) - Abi Younes, George; Ayoubi, Charles; Ballester, Omar; Cristelli, Gabriele; de Rassenfosse, Gaétan; Foray, Dominique; Gaulé, Patrick; Pellegrino, Gabriele; van den Heuvel, Matthias; Webster, Elizabeth; Zhou, Ling
Abstract: The present document provides the take of innovation economists on the COVID-19 pandemic. It targets the general public and focuses on questions related to the Science, Technology, and Innovation ecosystem. It provides a reading of current real-world developments using economic reasoning and relying on existing economic research.